2013
DOI: 10.1007/s00436-013-3650-6
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin L1 mimotopes with adjuvant Quil A induces a Th1/Th2 immune response and confers significant protection against Fasciola hepatica infection in goats

Abstract: Thirty goats were randomly allocated in five groups of six animals each, for immunization with 1 × 10(14) phage particles of clones 11, 13, and 13 with Quil A adjuvant and wild-type M13KE phage at the beginning and 4 weeks later. The control group received phosphate-buffered saline. All groups were challenged with 200 metacercariae at week 6 and slaughtered 14 weeks later. The mean worm burdens after challenge were reduced by 46.91% and 79.53% in goats vaccinated with clones 13 and 13 with Quil A (P < 0.05), r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 46 publications
1
23
0
1
Order By: Relevance
“…These observations confirm the notion that the vaccine potential of FhSAP2 is highly depending of the animal species and the experimental conditions. Trials on a number of vaccine candidates, glutathione S-transferase (Morrison et al, 1996; Sexton et al, 1990; Sexton et al, 1994), cathepsin L- proteases (Mulcahy et al, 1999; Villa-Mancera et al, 2014) and fatty acid binding proteins (Casanueva et al, 2001; Lopez-Aban et al, 2007; Martinez-Fernandez et al, 2004) have also shown a lack of consistency in the degree of protection obtained, which may be due, in part, to differences in the experimental design, for example route of immunization (injection or oral), form of antigen, presence of adjuvants in the vaccine and differences in the animal models (van Milligen et al, 2000; Vercruysse et al, 2004; Wedrychowicz et al, 2003). …”
Section: Discussionmentioning
confidence: 99%
“…These observations confirm the notion that the vaccine potential of FhSAP2 is highly depending of the animal species and the experimental conditions. Trials on a number of vaccine candidates, glutathione S-transferase (Morrison et al, 1996; Sexton et al, 1990; Sexton et al, 1994), cathepsin L- proteases (Mulcahy et al, 1999; Villa-Mancera et al, 2014) and fatty acid binding proteins (Casanueva et al, 2001; Lopez-Aban et al, 2007; Martinez-Fernandez et al, 2004) have also shown a lack of consistency in the degree of protection obtained, which may be due, in part, to differences in the experimental design, for example route of immunization (injection or oral), form of antigen, presence of adjuvants in the vaccine and differences in the animal models (van Milligen et al, 2000; Vercruysse et al, 2004; Wedrychowicz et al, 2003). …”
Section: Discussionmentioning
confidence: 99%
“…In vaccinated cattle, a Th1 response with high titres of IgG2 and low titres of IgG1 has been correlated with protection (Mulcahy et al., ). More recent trials in cattle (Golden et al., ), sheep (Maggioli et al., )and goats (Villa‐Mancera, Reynoso‐Palomar, Utrera‐Quintana, & Carreón‐Luna, ) found high levels of IgG2 and IgG1 associated with protection, possibly indicating a mixed Th1/Th2 response. As described in Section 7, Fasciola spp.…”
Section: Vaccine Developmentmentioning
confidence: 96%
“…Using CL1/CL2 mimitopes, Villa‐Mancera et al. () reported 47% protection in sheep, and CL1 mimitopes on their own led to protection of 51% in sheep (Villa‐Mancera & Méndez‐Mendoza, ) and 46%–79% in goats (Villa‐Mancera et al., ). These promising results in sheep and goats have yet to be validated in subsequent trials and in field trials.…”
Section: Vaccine Developmentmentioning
confidence: 99%
“…In the case of F. hepatica cathepsins, Harmsen et al (2004) described specific regions of FhCL1 and FhCL3 used to immunize rats which induced 40-64% fluke burden reduction [36]. Villa-Mancera (2008, 2011 and 2014) developed synthetic peptide mimotopes based on the FhCL1 protein sequence that could induce fluke burden reduction in sheep [37,38], mice [39] and goats [40]. In cattle, Cornelissen (1999) described peptides of FhCL1 that could be used as immunodiagnostics for F. hepatica infection [41].…”
Section: Introductionmentioning
confidence: 99%